Smashing mobile web development : going mobile with HTML5, CSS3, and Javascript - Avola, Greg; Raasch, Jon (Chichester, West Sussex, UK : John Wiley & Sons Inc., 2013)
"By the time you finish this book, you'll possess all the knowledge and skills you need to create sophisticated mobile websites incorporating the features your users want, including geolocation, social media, and much more."-- Back cover.
pt. I. Introduction to HTML5/JS/CSS -- Introduction to mobile web development -- Overview of mobile technologies -- pt. II. Application setup and infrastructure -- Development and production setup -- Creating the prototype -- Mobile web structure -- Creating a mobile web database -- pt. III. Development -- Interacting with web SQL -- Geolocation and AJAX -- Running queries and connecting with social media -- Location storage and seach -- pt. IV. Performance and production -- Testing and organizing your code -- Preparing for launch.
Includes index.
computer bookfair2015
Keywords: HTML (Document markup language); Cascading style sheets; Java (Computer program language); Mobile computing -- Programming; Application software -- Development